Gender Inequality in the Phenomenon of Victim Blamin in the Cases of Revenge Porn on Social Media: A Pragmatic Study - Triana Puspitasari; Febri Wulan Kirani; Ika Aulia Andri Saputri; Karisma Yudianti Putri (Journal of Feminism and Gender Studies, 2025)
Using digital platforms has many positive impacts on society, digital platforms also have a negative impact. One of them is the many crimes that have arisen as a result of technological advances, such as online gender-based violence, one of which is the asus victim blaming in revenge porn. The difference in response that occurs in victims of revenge porn can lead to gender inequality. Gender inequality is an injustice that occurs between men and women in aspects of life. Gender-based violence refers to women who are more vulnerable to various forms of violence, while gender stereotypes refer to people's perceptions of a particular gender. Based on this background, the purpose of this study is to describe the form of gender inequality in victim blaming in porn revenge cases on social media. This research uses a descriptive qualitative approach on exploration of human social problems. Based on the results of the study found forms of gender inequality in victim blaming in cases of revenge porn which are experienced by many women. It is also observed that gender inequality can be observed from the stereotypes that women receive, namely women receive negative labeling and rights difficulties while men accept information and the right to freedom.